Ubiquitin proteasome system in immune regulation and therapeutics. (December 2022) - Bhat, Sameer Ahmed; Vasi, Zahra; Adhikari, Ritika; Gudur, Anish; Ali, Asceal; Jiang, Liping; Ferguson, Rachel; Liang, David; Kuchay, Shafi
Abstract: The ubiquitin proteasome system (UPS) is a proteolytic machinery for the degradation of protein substrates that are post-translationally conjugated with ubiquitin polymers through the enzymatic action of ubiquitin ligases, in a process termed ubiquitylation. Ubiquitylation of substrates precedes their proteolysis via proteasomes, a hierarchical feature of UPS. E3-ubiquitin ligases recruit protein substrates providing specificity for ubiquitylation. Innate and adaptive immune system networks are regulated by ubiquitylation and substrate degradation via E3-ligases/UPS. Deregulation of E3-ligases/UPS components in immune cells is involved in the development of lymphomas, neurodevelopmental abnormalities, and cancers. Targeting E3-ligases for therapeutic intervention provides opportunities to mitigate the unintended broad effects of 26S proteasome inhibition. Recently, bifunctional moieties such as PROTACs and molecular glues have been developed to re-purpose E3-ligases for targeted degradation of unwanted aberrant proteins, with a potential for clinical use. Here, we summarize the involvement of E3-ligases/UPS components in immune-related diseases with perspectives.